Dietary intake and body composition of football players during the holy month of Ramadan - Maughan, R. J.; Bartagi, Z.; Dvorak, J.; Zerguini, Y. (Journal of Sports Sciences, 2008)
Healthy young male football players who were either fasting (n = 59) or not fasting (n = 36) during the month of Ramadan were studied. Body mass, body composition, and dietary intake were assessed at each time point. Energy intake was relatively stable in the fasting participants, but there was a small decrease of approximately 0.7 kg in body mass during Ramadan. Mean daily energy intake increased from 14.8 MJ (s = 2.9) to 18.1 MJ (s = 3.2) during Ramadan in non-fasting participants, with concomitant increases in body mass and body fat content of about 1.4 kg and 1% respectively over the month. The fractional intake of protein increased and the fractional contribution of carbohydrate decreased for both groups in Ramadan. Estimated mean daily water intake was high (about 3.8 litres) throughout the study period. Water intake increased on average by 1.3 litres · day-1 in line with the greater energy intake in the non-fasting group in Ramadan. Daily sodium intake fell during Ramadan in the fasting participants from 5.4 g (s = 1.1) before Ramadan to 4.3 g (s = 1.0) during Ramadan, but increased slightly by about 0.7 g · day-1 in the non-fasting group. Dietary iron decreased in the fasting group and increased in the non-fasting group, reflecting the difference in energy intake in both groups during Ramadan. These data suggest that Ramadan fasting had some effects on diet composition, but the effects were generally small even though the pattern of eating was very different. After Ramadan, the dietary variables reverted to the pre-Ramadan values.